Revised Species Delimitation in the Giant Water Lily Genus Victoria (Nymphaeaceae) Confirms a New Species and Has Implications for Its Conservation - Smith, Lucy T.; Magdalena, Carlos; Przelomska, Natalia A. S.; Pérez-Escobar, Oscar A.; Melgar-Gómez, Darío G.; Beck, Stephan; Negrão, Raquel; Mian, Sahr; Leitch, Ilia J.; Dodsworth, Steven; Maurin, Olivier; Ribero-Guardia, Gaston; et al. (Frontiers in Plant Science, 2022)
Reliably documenting plant diversity is necessary to protect and sustainably benefit from it. At the heart of this documentation lie species concepts and the practical methods used to delimit taxa. Here, we apply a total-evidence, iterative methodology to delimit and document species in the South American genus Victoria (Nymphaeaceae). The systematics of Victoria has thus far been poorly characterised due to difficulty in attributing species identities to herbarium specimens. This research gap stems from an absence of type material and biological collections, also the resulting confused diagnosis of V. cruziana. With the goal of improving systematic knowledge of the genus, we compiled information from historical records, horticulture and geography and assembled a morphological dataset using citizen science and specimens from herbaria and living collections. Finally, we generated genomic data from a subset of these specimens. Morphological and geographical observations suggest four putative species, three of which are supported by nuclear population genomic and plastid phylogenomic inferences. We propose these three confirmed entities as robust species, where two correspond to the currently recognized V. amazonica and V. cruziana, the third being new to science, which we describe, diagnose and name here as V. boliviana Magdalena & L.T.Sm.. Importantly, we identify new morphological and molecular characters which serve to distinguish the species and underpin their delimitations. Our study demonstrates how combining different types of character data into a heuristic, total-evidence approach can enhance the reliability with which biological diversity of morphologically challenging groups can be identified, documented and further studied.